PENGARUH WORKPLACE BULLYING DAN PERCEIVED SUPERVISOR SUPPORT TERHADAP TURNOVER INTENTION - Candra Vionela Merdiana; Bagus Gumelar (Jurnal Fokus Manajemen Bisnis, 2021)
This study aims to analyze the effect of Workplace Bullying and Perceived Supervisor Support on Turnover Intention of Employees of a Private University in Yogyakarta.. This research is a quantitative research through a survey method using a questionnaire. The sample in this study were some employees of a Private University in Yogyakarta with a total sample of 71 employees. The sampling technique in this study is non-probability sampling with the Incidental Sampling method. The unit of analysis used in this study is the individual, namely the employee of a Private University in Yogyakarta. This study uses an instrument test conducted with validity and reliability tests as a condition before testing the hypothesis, while the multiple regression analysis method is used to test the hypothesis. The results of hypothesis testing using multiple regression analysis indicate that the first hypothesis is accepted, namely the effect of work bullying has a positive and significant effect on turnover intentions, the second hypothesis is rejected, namely the influence of supervisor support perceptions has no significant effect on turnover intention.